2019
DOI: 10.33785/ijds.2019.v72i02.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex PCR for identification of mastitis causing organisms

Abstract: In the present study, a de novo multiplex polymerase chain reaction using genus specific primers for four organisms' viz., E. coli, Klebsiella pneumoniae, Staphylococcus aureus and Streptococcus agalactiae were designed to identify and differentiate all the four organisms in a single reaction. Further, DNA was extracted from mastitic milk using three different methods and was subjected to multiplex polymerase chain reaction to compare and identify the best method out of these three methods based on the amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results of our study are similar to findings of a study done by Hussein, (2012) that reported a positive bacterial isolation of 47 samples out of the total 61 milk samples that showed positive results by the CMT. Singh et al (2019) reported from a study that out of a total of 69 SLS positive samples 50 samples showed positive bacterial growth (72.46%) and Kulaste, ( 2019) observed 93.47% correlation between bacterial isolation and SLS test results. Similarly, very high correlation between isolation rate and CMT positive too has been reported by Heleili et al (2012) and Saidi et al (2013) of 87.25% and 98% respectively which is absolutely in tandem to the findings of this study.…”
Section: Isolation and Identification Of The Causative Agentsmentioning
confidence: 94%
“…The results of our study are similar to findings of a study done by Hussein, (2012) that reported a positive bacterial isolation of 47 samples out of the total 61 milk samples that showed positive results by the CMT. Singh et al (2019) reported from a study that out of a total of 69 SLS positive samples 50 samples showed positive bacterial growth (72.46%) and Kulaste, ( 2019) observed 93.47% correlation between bacterial isolation and SLS test results. Similarly, very high correlation between isolation rate and CMT positive too has been reported by Heleili et al (2012) and Saidi et al (2013) of 87.25% and 98% respectively which is absolutely in tandem to the findings of this study.…”
Section: Isolation and Identification Of The Causative Agentsmentioning
confidence: 94%